IMPROVEMENT STUDY RESULT OF SCIENCE THROUGH VISUAL AUDIO MEDIA IN SDN GUNUNG BUNDER 01 PAMIJAHAN BOGOR - Ria Rizki Agustini (Al-Mubin, 2024)
Most of the sixthgrade students at SDN Gunung Bunder 01 Pamijahan Bogor experience difficulties in learning Natural Sciences (IPA), especially in material for adapting living things to their environment. It was found that out of 18 students, only 8 students (44%) achieved KKM scores and those below KKM there were 10 students (66%). Where the KKM value determined by the school is 70. From the fact above, it is necessary to make efforts to further improve student learning outcomes in the material for adapting living things to their environment. One effort is to use audio-visual media in learning science. Research conducted using the Classroom Action Research approach Suharsimi Arikunto (2017: 19) defines Classroom Action Research as "Systemic Inquiry" conducted by teachers, principals, or school counselors to gather information about various schooling practices, including improving student learning outcomes. In the initial conditions (pre-cycle) student learning outcomes were very low, this was evidenced by the number of students who achieved KKM, only 8 students out of 18 students, with the lowest score being 40 and the highest score being 80. In cycle I it was seen that student learning outcomes had increased by 14 students who achieve KKM with the lowest score of 60 and the highest score of 100. In cycle II, student learning outcomes have improved well, this is based on formative test scores at the end of learning. 18 students (100%) experienced an increase in learning outcomes, although there was still 1 student (6%) who scored below the KKM. Using audio-visual media can improve student learning outcomes in science lessons on living things' adaptation to their environmen